THE ROLE OF SOCIAL MEDIA IN THE AGE DIGITAL DIPLOMACY (Third Sector Social Economic Review, 2025)
This research analyzes the impact of social media on digital diplomacy, highlighting how digital platforms have become essential tools for modern states and international actors. Digital diplomacy refers to communication processes conducted through digital channels rather than traditional methods and has been transformed by the rapid development of social media. Social media enables states and international organizations to accelerate information flow, directly reach large audiences, and respond effectively during crises. The study emphasizes the role of social media in public diplomacy, which aims to create a positive image of states and organizations among foreign societies. Social media plays a critical role in this process by providing access to wide audiences and facilitating direct interaction. By sharing content related to cultural events, diplomatic achievements, and national values, states seek to generate interest and influence among foreign publics. Additionally, the two-way communication enabled by social media fosters mutual engagement between governments and the public. Through document analysis, this study examines the role of social media in disseminating diplomatic messages, managing crises, and shaping international image. The findings highlight social media’s strong potential for crisis management, public engagement, and the construction of positive international perceptions.
Keywords: Social Media; Digital Diplomacy; Public Diplomacy; Crisis Management; Thematic Analysis.